A Karyomorphological Study on the Subgenus Leopoldia of the Genus Muscari Growing in Turkey - Kiran, Yasar; Pinar, Suleyman Mesut; Dogan, Gulden; Eroglu, Huseyin (Univ Tokyo Cytologia, 2020)
The chromosome numbers and karyotypes of 11 species the subgenus Leopoldia of the genus Muscari distributed in Turkey were analyzed. These taxa are M. comosum (L.) Miller, M. weissii Freyn, M. caucasicum (Griseb.) Baker, M. tenzeorum Tausch, M. babachii Eker & Koyuncu, M. erdalii Ozhatay & Demirci, M. longipes Boiss., M. massayanum Grunert, M. mirum Speta, M. elmasii Yildirim, and M. haradjiani Briq. ex Rech., and six of them (M. babachii, M. erdalii, M. massayanum, M. mirum, M. elmasii, M. haradjiani) are endemic species in Turkey. The somatic chromosome number of all studied taxa were determeined as 2n=2x=18. Haploid chromosome lengths varied 44.06 (M. massayanum) to 67.50 mu m (M. babachii) among species. Karyotype analysis indicated that Muscari taxa generally have median (m), submedian (sm) and subterminal (st) chromosomes. In addition, only M. comosum has one terminal (t) chromosome. Satellites were observed in five species, M. tenuiflorum, M. erdalii, M. longipes, M. mirum and M. haradjianii. This study is the first in terms of revealing the karyotypes of all taxa of subgenus Leopoldia on the genus Muscari.
Keywords: Muscari; Leopoldia; Karyotype; Chromosome number; Turkey